Architectures for wrist-worn energy harvesting. (5th March 2018) - Rantz, R; Halim, M A; Xue, T; Zhang, Q; Gu, L; Yang, K; Roundy, S
Abstract: This paper reports the simulation-based analysis of six dynamical structures with respect to their wrist-worn vibration energy harvesting capability. This work approaches the problem of maximizing energy harvesting potential at the wrist by considering multiple mechanical substructures; rotational and linear motion-based architectures are examined. Mathematical models are developed and experimentally corroborated. An optimization routine is applied to the proposed architectures to maximize average power output and allow for comparison. The addition of a linear spring element to the structures has the potential to improve power output; for example, in the case of rotational structures, a 211% improvement in power output was estimated under real walking excitation. The analysis concludes that a sprung rotational harvester architecture outperforms a sprung linear architecture by 66% when real walking data is used as input to the simulations.